Disease progression of non-alcoholic fatty liver disease: a prospective study with paired liver biopsies at 3 years - Wong, Vincent Wai-Sun; Wong, Grace Lai-Hung; Choi, Paul Cheung-Lung; Chan, Anthony Wing-Hung; Li, Mia Ka-Po; Chan, Hoi-Yun; Chim, Angel Mei-Ling; Yu, Jun; Sung, Joseph Jao-Yiu; Chan, Henry Lik-Yuen (Gut, 2010)
BackgroundPatients with non-alcoholic steatohepatitis (NASH) have increased mortality and liver-related complications. In contrast, simple steatosis is considered benign and non-progressive.ObjectiveTo investigate disease progression in patients with different degrees of non-alcoholic fatty liver disease (NAFLD) activity.DesignProspective longitudinal hospital-based cohort study.PatientsFifty-two patients (age 44±9 years) with biopsy-proven NAFLD had liver biopsies repeated at month 36.ResultsAmong 13 patients with simple steatosis at baseline, 2 (15%) had a normal liver at month 36, 3 (23%) continued to have simple steatosis, 5 (39%) developed borderline NASH and 3 (23%) developed NASH. Among 22 patients with borderline NASH at baseline, 4 (18%) had simple steatosis and 13 (59%) had borderline NASH at month 36, while 5 (23%) developed NASH. Among 17 patients with NASH at baseline, 10 (59%) continued to have NASH and 6 (35%) had borderline NASH at month 36. Only 1 (6%) patient regressed to simple steatosis. Overall, 14 (27%) patients had fibrosis progression, 25 (48%) had static disease, and 13 (25%) had fibrosis regression. Reduction in body mass index and waist circumference was independently associated with non-progressive disease activity and fibrosis. The baseline serum levels and month 36 changes in adiponectin, tumour necrosis factor α, interleukin 6 and leptin were not associated with disease progression. Serum cytokeratin-18 fragment level reflected disease activity and its change correlated with the change in NAFLD activity score (R=0.51, p<0.001).ConclusionsPatients with simple steatosis may still develop NASH and fibrosis progression. Weight reduction is associated with non-progressive disease. All patients with NAFLD should undergo periodic assessment and lifestyle modification.